The Influence Of High-Performance Work Systems And Servant Leadership On Organizational Performance Through The Mediation Role Of Employee Work Engagement At Bank Indonesia Representative Aceh - Jaya, Wahyu Indra; Matriadi, Faisal; Faliza, Nur; Marbawi, Marbawi; Mariyudi, Mariyudi; Ikramuddin, Ikramuddin; Arifin, A. Hadi (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2024)
The purpose of this research is to examine the influence of high-performance work systems and servant leadership on organizational performance through the mediating role of employee engagement at Bank Indonesia Lhokseumawe Representative Office. The data in this research were 133 employees who responded to the questionnaire distributed via Google Forms. The data analysis tool uses Structural Equation Modeling (SEM) which is operated with Amos. The research results found that High-Performance Work Systems (HPWS) and Servant Leadership have a significant effect on employee engagement and employee performance. Employee engagement also significantly improves employee performance. In testing the mediating effect of employee engagement, it became a partial mediating variable between High-Performance Work Systems (HPWS) and Servant Leadership on the performance of Bank Indonesia Aceh Representative employees. It is hoped that the results of this research will provide an important contribution to stakeholders in developing employee development strategies as an important resource for every organization.